1992
DOI: 10.1016/s0168-1591(05)80063-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of housing conditions on beagle behaviour

Abstract: Behaviours studied were movement, vocalisation, lying down, sleep, object manipulation, barrier manipulation, barrier jumping, fence running, agonistic and affiliative activities, and proximity. Behavioural effects were compared among housing conditions, order of rotation through each housing condition, and behavioural changes over time during each 3 month rotation.Dogs spent more time moving in pens and runs than in cages. Dogs housed in the greatest degree of social isolation spent the most time moving, exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
68
7
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(104 citation statements)
references
References 10 publications
5
68
7
5
Order By: Relevance
“…Noise is absorbed and contained within the smaller room. These designs may also permit social housing of dogs, which research has shown to decrease noise caused by animal vocalization and increase the time animals spend sleeping (Hetts, Clark, Calpin, Arnold, & Mateo, 1992;Mertens & Unshelm, 1996). The incorporation of areas for play groups can contribute to noise abatement, as a mentally and physically exercised dog usually is a quiet one (personal communication, November 17, 2005; San Francisco Society for the Prevention of Cruelty to Animals, American Society for the Prevention of Cruelty to Animals, Humane Society at Lollypop Farm, Denver Dumb Friends League, North Shore Animal League).…”
Section: Discussionmentioning
confidence: 99%
“…Noise is absorbed and contained within the smaller room. These designs may also permit social housing of dogs, which research has shown to decrease noise caused by animal vocalization and increase the time animals spend sleeping (Hetts, Clark, Calpin, Arnold, & Mateo, 1992;Mertens & Unshelm, 1996). The incorporation of areas for play groups can contribute to noise abatement, as a mentally and physically exercised dog usually is a quiet one (personal communication, November 17, 2005; San Francisco Society for the Prevention of Cruelty to Animals, American Society for the Prevention of Cruelty to Animals, Humane Society at Lollypop Farm, Denver Dumb Friends League, North Shore Animal League).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays this simplistic idea is accepted less frequently (Hetts et al 1992;Houpt and Willis 2001) but as stated by Fraser and Rushen (1987), it still survives. Presently, the circumstances under which aggression occurs become more emphasized.…”
mentioning
confidence: 99%
“…dogs, foxes) exploring the linkage between increased available space or increased number of animals within a housing unit and activity level have led to contradictory conclusions. As the amount of space available increases, the activity level of the animals has either increased (dog: Hetts et al 1992), remained constant (raccoon dog: Korhonen and Harri 1988), or decreased (dog: Hughes et al 1989). Increasing the number of animals within a housing unit, which usually means also increasing the total available area for the members of the group, has typically increased the activity level of the animals (dog: Hubrecht et al 1992;silver fox: Bakken et al 1994, Ahola et al 2000, but see dog: Hetts et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…As the amount of space available increases, the activity level of the animals has either increased (dog: Hetts et al 1992), remained constant (raccoon dog: Korhonen and Harri 1988), or decreased (dog: Hughes et al 1989). Increasing the number of animals within a housing unit, which usually means also increasing the total available area for the members of the group, has typically increased the activity level of the animals (dog: Hubrecht et al 1992;silver fox: Bakken et al 1994, Ahola et al 2000, but see dog: Hetts et al 1992). In the present study, neither increasing space allocation (0.6 m 2 vs. 1.2 m 2 ) nor increasing the number of animals within a housing unit (one vs. two vs. four) evoked any differences in activity levels of the animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation